EMPLOYABILITY SKILL AND CAREER CHOICES AMONG VOCATIONAL SKILL STUDENTS - Zakaria.N,; Ismail.N,; Yamin.NA, (Online Journal for TVET Practitioners, 2017)
Employability Skills terminology is widely used in many countries it is the basic skills needed in the 21st century. This study aims to look at the relationship between career choices employability skills among vocational skill student. This study participated by 106 third year vocational students in vocational colleges participated in this study. The instrument used was a questionnaire. Data were analyzed by descriptive and inferential. The findings of the relationship employability skills with career choices recorded value is .742, which also proved a strong relationship between these variables. In conclusion, the employability skills are need to be improved by applying more effective by the vocational training to ensure they are eligible for employment after graduation. The study also proved that the employability skills of students affect them more likely to choose a career in the same field with the course they have chosen.